Utilization of Internet-Based School TV Media as an Educational Media and Means of Documenting Student’s Artwork at SMP Frater Padang - Fauzan Yusman, Ahmad; Ardipal, Ardipal; Efi, Agusti; Mansyera Pratama, Vischa; Aulya, Vinna (SENDRATASIK UNP, 2024)
This article discusses the use of internet-based school TV media as a means of educational media and a means of documentation of students' artworks at Brother Padang Junior High School. The research method uses qualitative research with a descriptive analysis approach. Data collection techniques used in this study used observation techniques, documentation studies and interviews. This research found that Frater Junior High School Padang developed school TV by utilizing the internet with the Youtube platform. Students of Frater Junior High School Padang are given media to utilize technology in operating and producing audio-visual media. Apart from being an educational tool, Frater TV is also utilized in documenting the artwork of students in the form of various performing arts, such as vocal, choir, dance and theater. From this utilization, students have direct experience in using technological media as well as documentation of cultural works of art.